What time the Sexton's spade doth rust - Bradley, Alan, 1938- (Bradley, Alan, 1938- Flavia de Luce mystery., 2024)
"Flavia de Luce has taken on the mentorship of her odious, moon-faced cousin Undine, who has come to live at Buckshaw following the death of her mother. Undine's main talent, aside from cultivating disgusting habits, seems to be raising Flavia's dander, although in her best moments she shows potential for trespassing, trickery, and other assorted mayhems. When Major Greyleigh, a local recluse and former hangman, is found dead from a breakfast of poisonous mushrooms, suspicion falls on the de Luce family's longtime cook, Mrs. Mullet. After all, wasn't it she who picked the mushrooms, cooked the omelette, and served it to Greyleigh in the moments before his death? "I have to admit," says Flavia, an expert in the chemical nature of poisons, "that I'd been praying to God for a jolly good, old-fashioned mushroom poisoning. Not that I wanted anyone to die, but why give a girl a gift such as mine without giving her the opportunity to use it?" But Flavia knows the beloved Mrs. Mullet is innocent. Together with Dogger, estate gardener and partner-in-crime, and the obnoxious Undine, she sets out to find the real killer and clear Mrs. Mullet's good name. Little does she know that following the case's twists and turns will lead her to a most surprising discovery--one with the power to upend her entire life"--